The STAC Model: Rethinking the Basic Functionality of Informal Learning Spaces - Tom Haymes (Arizona State University, 2020)
Productive "Third Spaces" are often an afterthought when designing learning environments, both in a physical sense and online. These areas, properly mediated by technology and designed around humans, can often be a key facilitator for student success. The STAC Model is designed to provide a framework for understanding what makes these spaces successful in capturing and retaining students who would otherwise leave the learning environment at the first opportunity. STAC stands for "Stickiness, Toolsets, Adjacencies, and Community" and is an order of priority system for prioritizing design and technological elements within any space. This article describes the rationale behind the model and how it can be applied in both physical and online environments.